Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

g(x)=x-1/x f(g(x))=x^3-1/x^3 then prove that f(x)=3x^2+3

g(x)=x-1/x   f(g(x))=x^3-1/x^3


then prove that f(x)=3x^2+3

Grade:11

1 Answers

pankaj dave
18 Points
8 years ago

f(g(x))=(x-1/x)3+3(x.1/x)(x-1/x)

 f(y)  =y3+3y        y=x-1/x

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free